USING RAINBOW SONG TO INTRODUCE ENGLISH COLOR VOCABULARIES; A CASE OF THE SECOND GRADE STUDENTS OF KINDERGARTEN “TARBIYATUL ATHFAL 04 SABILUN NAJAH” PENJALIN BRANGSONG KENDAL - Rofika Lestari (ETERNAL (English Teaching Journal), 2014)
This research is based on the study which attempted to introduce English color vocabularies using rainbow song. The objectives of the study were: (1) To find out the teacher’s way in applying English color vocabularies through rainbow song. (2) To find out the teacher’s problems in applying rainbow song to introduce English color vocabularies. (3) To identify the teacher’s solution in solve the problems. This study is a descriptive qualitative research. The object of the research were the second grade students and teachers of Kindergarten “Tarbiyatul Athfal 04 Sabilun Najah” Penjalin Brangsong Kendal. The writer took 20 students and 2 teachers of group B as object of the research. The instruments of this research were observation sheet and questionnaire. In this study, the writer collected the data from field research. The writer conducted a classroom observation activity and gave questionnaires to the teachers after the lesson finished. The writer found that the teachers implemented the use of rainbow song as a media in introducing English color vocabularies through three activities, they were: pre-activity, main-activity, and post-activity. In main-activity, the teacher showed the material used video compact disc and gave pictures to paint by the students to match between pictures with the colors. In post-activity, the teachers asked the students one by one about colors in the picture that they have painted. The writer found some problems faced by the teachers. The students difficulty to concentrate in the teaching learning process. The students didn’t speak well. The students’ difficulties to understand English color vocabularies. The writer also found some possible solutions to overcome the problems faced by the teacher. The teachers should give example not only one, but also more than one. The teachers should ask the students to do some exercise of vocabulary to improve their proficiency in English skill. The teachers should be able to give attention to the students. The teachers should be creative to find or create the English teaching method especially vocabulary, that attracts the kindergarten students. The teachers should give the students different experience and reinforcement, and the teachers practice the teaching material vocabulary to students day by day. The teachers should encourage the students to learn vocabulary.